Integration analysis of metabolome and transcriptome reveals the effect of exogenous supplementation with mixtures of vitamins ADE, zinc, and selenium on follicular growth and granulosa cells molecular metabolism in donkeys (Equus asinus) - Guo, Yajun; Zhao, Weisen; Li, Nan; Dai, Shizhen; Wu, Hao; Wu, Zhenlong; Zeng, Shenming (Frontiers in Veterinary Science, 2022)
Vitamins and trace elements play essential roles in mammalian ovarian physiology, including follicle development, ovulation, and synthesis and secretion of hormones and growth factors. However, it is nevertheless elusive to what extent exogenous supplementation with mixtures of vitamins ADE, Zn, and Se affects follicular growth and granulosa cells (GCs) molecular function. We herein investigated their effect on follicular growth and GCs physiological function. We showed that follicular growth and ovulation time was accelerated and shortened with the increases of vitamins ADE, zinc (Zn), and selenium (Se) doses by continually monitoring and recording (21days) with an ultrasound scanner. Integrated omics analysis showed that there was a sophisticated network relationship, correlation expression, and enrichment pathways of the genes and metabolites highly related to organic acids and their derivatives and lipid-like molecules. Quantitative real-time PCR (qPCR) results showed that VDR, TRPM6, TRPV6, SLC5A1, ALOX5, STAR, PTGS2, and IGF-1 had a strong correlation between the transcriptome data. Combined multi-omics analysis revealed that the protein digestion and absorption, ABC transporters, biosynthesis of amino acids, aminoacyl-tRNA biosynthesis, mineral absorption, alanine, aspartate and glutamate metabolism, glycine, serine and threonine metabolism, arginine biosynthesis, and ovarian steroidogenesis were significantly enriched. We focused on the gene-metabolite interactions in ovarian steroidogenesis, founding that INSR, PLA2G4A, ADCY6, CYP1B1, PRKACB, CYP17A1, and PLA2G4F were negatively correlated with β-estradiol, progesterone, and testosterone (P < 0.05). while ALOX5 was a positive correlation with β-estradiol and progesterone testosterone (P < 0.05); CYP19A1 was a negative correlation with cholesterol (P < 0.01). In mineral absorption, our findings further demonstrated that there was a positive correlation between SLC26A6, SLC5A1, and SLC6A19 with glycine and L-methionine. SLC40A1 was a negative correlation with glycine and L-methionine (P < 0.01). TRPV6 and ATP1A1 were positively associated with glycine (P < 0.05); while ATP1B3 and CYBRD1 were negatively related to L-methionine (P < 0.05) These results suggested that the vitamins ADE, Zn, and Se of mixtures play an important role in the synthesis and secretion of steroid hormones and mineral absorption metabolism pathway through effects on the expression of the key genes and metabolites in GCs.